Extensive pyoderma gangrenosum in a 3-year-old boy. - Badabagni, P.; Singh, S.; Mavoori, A.; Pamar, S.; Ramadevi,; Bhamidipati, H.S. (European Journal of Pediatric Dermatology, 2024)
Pyoderma gangrenosum (PG) is a rare inflammatory and ulcerative skin disorder often associated with inflammatory bowel disease, arthritis, and hematologic malignancies. It is characterized by painful, necrotic ulcers with violaceous borders. The disease is estimated to occur in 3 to 10 people per million per year, predominantly affecting adults between 20 and 50 years of age, with a possible higher incidence in women. The current report describes a 3-year-old boy with extensive PG lesions, an unusual presentation in pediatric age. The patient was treated with systemic corticosteroids, cyclosporine, and supportive care, including oral antibiotics and topical corticosteroid creams, which resulted in significant improvement after 2 weeks.